The CANadian Pediatric Weight management Registry (CANPWR): lessons learned from developing and initiating a national, multi-centre study embedded in pediatric clinical practice - Katherine M. Morrison; Geoff D. C. Ball; Josephine Ho; Pam Mackie; Annick Buchholz; Jean-Pierre Chanoine; Jill Hamilton; Anne-Marie Laberge; Laurent Legault; Lehana Thabane; Mark Tremblay; Ian Zenlea (BMC, 2018)
Abstract Background There is increasing recognition of the value of "real-world evidence" in evaluating health care services. Registry-based, observational studies conducted in clinical settings represent a relevant model to achieve this directive. Starting in 2010, we undertook a longitudinal, observational study (the CANadian Pediatric Weight management Registry [CANPWR]), which is embedded in 10 multidisciplinary, pediatric weight management clinics across Canada. The objective of this paper was to share the lessons our team learned from this multi-centre project. Methods Data sources included a retrospective review of minutes from 120 teleconferences with research staff and investigators, notes taken during clinical site visits made by project leaders, information from quality control processes to ensure data accuracy and completeness, and a study-specific survey that was sent to all sites to solicit feedback from research team members (n = 9). Through an iterative process, the writing group identified key themes that surfaced during review of these information sources and final lessons learned were developed. Results Several key lessons emerged from our research, including the (1) value of pilot studies and central research coordination, (2) need for effective and regular communication, (3) importance of consensus on determining outcome measures, (4) challenge of embedding research within clinical practice, and (5) difficulty in recruiting and retaining participants. The sites were, in spite of these challenges, enthusiastic about the benefits of participating in multi-centre collaborative studies. Conclusion Despite some challenges, multi-centre observational studies embedded in pediatric weight management clinics are feasible and can contribute important, practical insights into the effectiveness of health services for managing pediatric obesity in real-world settings.